Quercetin Down-regulates IL-6/STAT-3 Signals to Induce Mitochondrial-mediated Apoptosis in a Non-small-cell Lung-cancer Cell Line, A549 - Avinaba Mukherjee; Anisur Rahman Khuda-Bukhsh (Korean Pharmacopuncture Institute, 2015)
Objectives: Quercetin, a flavonoid compound, has been reported to induce apoptosis in cancer cells, but its anti-inflammatory effects, which are also closely linked with apoptosis, if any, on non-small-cell lung cancer (NSCLC) have not so far been critically examined. In this study, we tried to determine if quercetin had any demonstrable anti-inflammatory potential, which also could significantly contribute to inducing apoptosis in a NSCLC cell line, A549. Methods: In this context, several assays, including cytotoxicity, flow cytometry and fluorimetry, were done. Gene expression was analyzed by using a western blot analysis. Results: Results revealed that quercetin could induce apoptosis in A549 cells through mitochondrial depolarization by causing an imbalance in B-cell lymphoma 2/Bcl2 Antagonist X (Bcl2/Bax) ratio and by down-regulating the interleukine-6/signal transducer and activator of transcription 3 (IL-6/STAT3) signaling pathway. An analysis of the data revealed that quercetin could block nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) activity at early hours, which might cause a down-regulation of the IL-6 titer, and the IL-6 expression, in turn, could inhibit p-STAT3 expression. Down-regulation of both the STAT3 and the NF-κB expressions might, therefore, cause down-regulation of Bcl2 activity because both are major upstream effectors of Bcl2. Alteration in Bcl2 responses might result in an imbalance in the Bcl2/Bax ratio, which could ultimately bring about mitochondria mediated apoptosis in A549 cells. Conclusion: Overall, the finding of this study indicates that a quercetin induced anti-inflammatory pathway in A549 cells appeared to make a significant contribution towards induction of apoptosis in NSCLC and, thus, may have a therapeutic use such as a strong apoptosis inducer in cancer cells.